Thyroid hormones for euthyroid patients with simple goiter growing over time: a survey of European thyroid specialists - Papini, Enrico; Attanasio, Roberto; Žarković, Miloš; Nagy, Endre Vezekenyi; Negro, Roberto; Perros, Petros; Galofré, Juan Carlos; Cohen, Chagit Adler; Akarsu, Ersin; Alevizaki, Maria; Ayvaz, Göksun; Bednarczuk, Tomasz; et al. (Endocrine, 2024)
Treatment of simple goiter (SG) growing over time with thyroid hormone (TH) therapy is discouraged by international guidelines.